MENGULIK PERAN JOB INSECURUTY YANG MEMPENGARUHI EMOTIONAL EXHAUSTIONAL PADA GEN Z DI DUNIA KERJA YANG DIMEDIASI OLEH DETERMINAN ROLE AMBIGUITY - Nurhasanah; Mustika Ratu; Sulistyo Utami; Kartin Aprianti (Jurnal Manajemen, 2023)
Emotional exhaustion is individual fatigue related to personal feelings and depletion of emotional resources, which refers to excessive emotional feelings due to contact with other people or work. Emotional exhaustion can be influenced by factors including job insecurity and role ambiguity. This research aims to determine the influence of job insecurity through role ambiguity which consists of unclear rules, vague responsibilities, vague expectations on emotional exhaustion at work. The sample in this research was Gen Z who worked part time, full time or freelance, amounting to 200 respondents. The data collection technique uses a list of questions such as a questionnaire and the data analysis technique uses Partial Least Square (SmartPls) to test the ten hypotheses proposed in this research. The research results show that job insecurity directly and indirectly through the determinants of role ambiguity has a positive and significant influence on emotional exhaustion.